Pharmaceutical Supply chain Risk Assessment During COVID-19 Epidemic. Issue 10 (2022) - BenAmor, W. Daoud; Labella, A.; Frikha, H. Moalla; López, L. Martínez
Abstract: The global health products supply chain is negatively influenced by the COVID-19 pandemic. Moreover, the risks in the pharmaceutical supply chain (PSC) have increased. Assessment and mitigation risks in PSC are essential issues to control and counter these risks. In this study, a 2-Tuple ARAS-BWM approach, which combines ARAS and BWM methods under linguistic 2-Tuple environment, is proposed to evaluate and address various risks to the best mitigation strategies in the pharmaceutical industry in Tunisia during COVID-19. Noted that the main risk identified in the PSC is related to supply and suppliers and its best mitigation strategy is reducing risk.